Forecasting Covid-19 Positive Cases Among Eight Asian Countries - Kastury Gohain , Manah Chandra Changmai (International Journal of Advanced Science and Technology, 2020)
The innovative method of forecasting helps authorities to take important decision on the cases of novel coronavirus on its effect, with prevention measures and planning of any possible outbreak. Publicly available data from different regions of the world can be studied through statistical methods for future prediction and hence can be projected to locate various other parameters to specify the reasons of spread or control of the disease. Recently figures witnessed not only steep peak for the number of positive coronavirus cases conjointly divulged alarming number of fatalities. According to the US Centers for Disease Control and prevention (CDC), handling the spread necessitates significant reduction in the number of new positive cases emergence. Thus the forecast of new number of positive case will facilitate the overburdening healthcare resources and infrastructure, thereby saving lives. Additionally this study offers a statistical technique to forecast future values which can to use to control pandemic like situation in future.